Installation art in the context of Métodos Artísticos Educadores (MAES). An analysis based on experiences with students from Teacher Education Degrees - Caeiro Rodríguez, Martín; Fuentes Cid, Sara; Covaleda Vicente, Irene; Fayos Bosch, Leticia; Zarzoso López, Pedro José (Pulso. Revista de educación, 2024)
In Artistic Teaching Methodologies (MAE) or Artistic Educational Methods (MAES), we find an ideal context for involving teacher training students in methods that articulate the contemporary nature of art and education, such as installations. These methodologies, rooted in the artistic field, promote teaching and learning through the creation and development of different artistic-educational projects. The present study is part of a Teaching Innovation Project implemented in the Infant and Primary Teaching Degrees. Its purpose is to explore the impact of Artistic Educational Methods on student teachers through the creation of installations. A detailed analysis is carried out, covering the type of installations, the experiences generated, the learning acquired, and the difficulties encountered. The results allow us to conclude that students understand the value and possibilities of working with art installations in their future teaching. At the same time, they are aware of the obstacles that can be encountered both in the conception and implementation of this type of proposal.